Il mito come strumento di scrittura contemporanea nei romanzi di Alain Nadaud - Galli Pellegrini , Rosa (Amaltea. Revista de Mitocrítica, 2009)
Alain Nadaud literary work can be rightly defined as a contemporary proposal for philosophical novel. In particularly, during his fiction journey Nadaud constantly pursues a search about the origin, the essence and the sense of writing. To pass on the content of such topics, extremely relevant in contemporary philosophical thinking, the writer plenty reutilizes mythological themes well known by western readers.